Nitric acid trihydrate nucleation and denitrification in the Arctic stratosphere - Grooss, Jens-Uwe; Engel, Ines; Borrmann, Stefan; Frey, W.; Günther, G.; Hoyle, Christopher; Kivi, Rigel; Luo, B.P.; Molleker, S.; Peter, Thomas; Pitts, C.M.; Schlager, Hans; et al. (Atmospheric Chemistry and Physics, 2014)
Nitric acid trihydrate (NAT) particles in the polar stratosphere have been shown to be responsible for vertical redistribution of reactive nitrogen (NOy). Recent observations by Cloud–Aerosol Lidar with Orthogonal Polarization (CALIOP) aboard the CALIPSO satellite have been explained in terms of heterogeneous nucleation of NAT on foreign nuclei, revealing this to be an important formation pathway for the NAT particles. In state of the art global- or regional-scale models, heterogeneous NAT nucleation is currently simulated in a very coarse manner using a constant, saturation-independent nucleation rate.